Lateral-torsional buckling of wide-flange beams - Su, Shiann-min; Morino, Shosuke; Karasudhi, Pisidhi; Cook, David J.; Takemiya, Hirokazu; The Government of the Republic of China (Bangkok : Asian Institute of Technology, 1976)
Investigated in this study are the elastic and inelastic lateral torsional buckling strengths of wide-flange beams with various boundary conditions subjected to proportionally applied end moments and uniformly distributed load in the plane of the web. The coupled differential equations governing the out-of-plane deflections of the beam buckling in the lateral-torsional manner are derived based on the assumption that no strain-reversed takes place during buckling. Application of finite difference expressions of the governing differential equations yields a set of homogeneous simultaneous equations, the out-of-plane displacements and angles of twist at subdivision points along the beam being unknown. The critical value of the normalized slenderness ratio of the beam under a given value of the loading parameter is numerically obtained as the one that makes the coefficient matrix of the simultaneous equations singular. The numerical results of the parametric study are presented in the form of the maximum moment carrying capacity - the normalized slenderness ratio curves, and they are compared with those given by approximate formulas previously proposed. As a conclusion, a set of simple formulas for the determination of the lateral-torsional buckling strength of elastic and inelastic wide-flange beams are proposed for the practical pur poses.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering of the Asian Institute of Technology, Bangkok, Thailand
Thesis (M.Eng.) - Asian Institute of Technology, 1976
Keywords: Structural stability; Girders; Buckling (Mechanics)